Fragile minds, porous selves: Shining a light on autoethnography of mental illness. (January 2023) - Fixsen, Alison
This article sheds light on autoethnographic accounts of mental illness, to address author and reader concerns and questions and to consider what practitioners can learn from these narrative accounts. Drawing from my own and others' trajectories, I discuss the drawbacks and dangers of exposing a 'flawed' identity, the stigma of serious mental illness, intertextuality issues, the tangled nature of revelation and redemption, framing the 'Other' in mental illness autoethnography and depictions of 'life in the asylum.' I explain how in telling my own 'psychiatric' tale, I looked to the symbolic concept of 'communitas' as a means of examining inter-relational processes and collective experience in a psychiatric facility. I argue that, while the act of writing about one's illness experience can be rightly perceived as a way of reclaiming personal 'power' and facilitating healing, attempts to 'evidence' recovery can run counter to the writer's reality of life with or beyond mental illness as personally and socially messy. In answer to the question, 'at what point does a 'life in the asylum' narrative become autoethnographic?' I argue for the potential of autoethnography to contribute to broader sociological, ethnographic and medical debates and thus impact on policy. Speaking up about mental health through autoethnography can help to promote awareness of the unpredictability and socially constructed nature of mental illness and can inform strategies toward reducing public stigma, tackle the cyclical impact of labels, highlight the need to change social and medical attitudes, and revisualize treatment and support.